CFD investigation of the in-situ gasification process of biomass in the chemical looping combustion system. (February 2022) - Dong, Ruihan; Yang, Shiliang; Hu, Jianhang; Chen, Fangjun; Bao, Guirong; Wang, Hua
Abstract: At present, chemical looping combustion has emerged as a promising combustion technology for carbon capture. In this work, the gas-solid reactive flow in the biomass gasification of the fuel reactor of the chemical looping combustion system is numerically studied via the multiphase particle-in-cell approach under the Eulerian-Lagrangian framework. Regarding the model validation, the gaseous products numerically obtained quantitatively agree well with the experimental data in the literature. Then, the gas-solid reactive flow behaviour together with the effect of operating parameters are discussed. The results show that the non-uniform distribution of solid phase along the axial direction results from the size/density-induced segregation, which gives rise to the accumulation of oxygen carrier particles in the bottom and elutriation of biomass particles. The skewed distribution of biomass residence time in the fuel reactor can be observed. The smallest carbon content exists in the region close to the feeding port. Above the feeding position, the increase of carbon content but the decrease of biomass mass can be observed. Compared with oxygen carriers, biomass particles have a larger dispersion coefficient. Small content of CO and H2 appears while a wide range of CO2 exists in the dense region of the reactor. Graphical abstract: Image 1